Evaluation and implementation of multidisciplinary, standardized, guideline-based long-term follow-up care for adult survivors of childhood cancer in Germany: protocol of a prospective, multi-center, nationwide study (LE-Na) - Cytera, C.; Baust, K.; Borgmann-Staudt, A.; Calaminus, G.; Egger-Heidrich, K.; Faber, J.; Grabow, D.; Halbsguth, T.; Kock-Schopenhauer, A.; König, I. R.; Michaelis, S.; Neumann, A.; et al. (BMC Cancer, 2025)
Background: Late effects can occur years to decades after cancer therapy, resulting in morbidity and reduced health-related quality of life. Clinical long-term follow-up (LTFU) enables timely diagnosis and treatment of these sequelae. So far, only a minority of childhood cancer survivors (CCS) in Germany regularly visit LTFU care facilities. The LE-Na study aims to: 1. implement and/or improve LTFU care structures for adult CCS in Germany, 2. inform former patients about late effects and LTFU care centers, 3. create a basis for future research by building up a central database, consent management and infrastructure, 4. establish a clinical LTFU cohort of adult CCS in Germany, 5. evaluate the implementation of the LFTU care, 6. enable the expansion of LTFU care structures nationwide, 7. integrate the developed LTFU care structures into the standard health care system. Methods: Within five years, approximately 5000 CCS will be invited to visit one of the 10 LTFU centers in Germany. Study participants are either contacted by the German Childhood Cancer Registry (GCCR), transitioned from the local pediatric oncology care unit, or recruited via media. They are assigned to one of three different risk groups based on an evidence-based risk stratification and receive standardized multidisciplinary follow-up care. Primary outcomes are satisfaction with the LTFU care offer as well as degree of health-related self-efficacy expectation. They will be assessed at two time points. A scientific evaluation of the implemented LTFU care will be enabled by a waitlist control group. The harmonized outcome data are documented in a standardized database. Discussion: By addressing CCS in Germany who have not received standardized LTFU care yet, the LE-Na study expects to improve nationwide LTFU care and therewith patient’s satisfaction with the LTFU care offer as well as their health-related self-efficacy expectation.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Childhood cancer survivors; Late effects; Long-term follow-up